2015
DOI: 10.2116/analsci.31.561
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Use of LC-ICP-MS and LC-ESI-Q-TOF-MS for Selenium Speciation

Abstract: Experimental ReagentsSodium selenate and ammonium acetate were purchased from Wako (Osaka, Japan).L-Selenomethionine (SeMet) and trimethylselenonium iodide (TMSe) were purchased from Sigma (St. Louis, MO) and Tri Chemical Laboratories, Inc. 2015 © The Japan Society for Analytical Chemistry † To whom correspondence should be addressed. E-mail: ogra@chiba-u.jp Complementary Use of LC-ICP-MS and LC-ESI-Q-TOF-MS for Selenium SpeciationYasumi ANAN,* Genki NAKAJIMA,* and Yasumitsu OGRA* , ** † We demonstrated the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 17 publications
(15 reference statements)
0
4
0
1
Order By: Relevance
“…Anan et al reported on "Complementary Use of LC-ICP-MS and LC-ESI-Q-TOF-MS for Selenium Speciation", describing the analytical performance of these techniques for Se-containing compounds, such as selenate, selenomethionine (SeMet), and trimethylselenonium ion (TMSe). 9 This study indicated that the sensitivity of LC-ICP-MS was higher than that of LC-ESI-Q-TOF-MS. Iwai et al reported on "Arsenic Speciation and Cadmium Determination in Tobacco Leaves, Ash and Smoke". 10 Tobacco leaves, ash, and smoke samples were prepared and the concentrations of As and Cd were determined after microwave-assisted digestion.…”
mentioning
confidence: 78%
“…Anan et al reported on "Complementary Use of LC-ICP-MS and LC-ESI-Q-TOF-MS for Selenium Speciation", describing the analytical performance of these techniques for Se-containing compounds, such as selenate, selenomethionine (SeMet), and trimethylselenonium ion (TMSe). 9 This study indicated that the sensitivity of LC-ICP-MS was higher than that of LC-ESI-Q-TOF-MS. Iwai et al reported on "Arsenic Speciation and Cadmium Determination in Tobacco Leaves, Ash and Smoke". 10 Tobacco leaves, ash, and smoke samples were prepared and the concentrations of As and Cd were determined after microwave-assisted digestion.…”
mentioning
confidence: 78%
“…A technical note which reports the advantages and disadvantages of ICP-MS and ESI-MS for Se speciation in biological samples has been presented this year. 169 The article includes a summary table with information on LOD values and sensitivity provided by ICP-MS and ESI-QTOF-MS for the determination of Se VI , SeMet and TMSe. Based on their own experimental data, the authors underline that the most effective use of ESI-MS is for species identication in conjunction with ICP-MS for species quantitation.…”
Section: Seleniummentioning
confidence: 99%
“…17 However, high (>levels of iodate 600 mg day -1 ) have been shown to cause ocular toxicity by damaging the retina. 18 At present, the studies of element species in water and food samples were mostly focused on the analysis of single element, [19][20][21][22][23][24] and there are few reports on simultaneous analysis of multielement species. The simultaneous analysis and determination of multi-element species can significantly improve the analysis efficiency and save testing costs.…”
Section: Introductionmentioning
confidence: 99%